PHYTOCHEMICAL, PROXIMATE, AND METAL CONTENT ANALYSIS OF CITRULLUS LANATUS (WATERMELON) SEED. - Imafidon, K. E.; Abu, O. D.; Obayuwana, H. O.; Okuofu, E. D. (FUDMA Journal of Sciences, 2023)
The present study examined the phytochemical, proximate and metal content of Citrullus lanatus (watermelon) seed. The dried seeds were pulverized into fine powder and a portion of it was extracted with methanol, and distilled water, and freeze-dried using a lyophilizer. The results of phytochemical screening showed that the seeds contained terpenoids, glycosides, steroids, alkaloids, flavonoids, coumarins and quinones in high amount, while phlobatannins and anthraquinones were not detected. Proximate analysis indicated low moisture content (10.40 ± 0.10 %), ash (6.60 ± 0.20 %), crude fat (14.60 ± 0.25 %), fibre (42.80 ± 1.80), high protein (7.70 ± 0.16%), and nitrogen-free extracts (NFE) (18.30 ± 1.35%), while metal analysis showed the presence of sodium (30.60 ± 0.25 mg/kg), calcium (0.97 ± 0.04 mg/kg), zinc (0.25 ± 0.00 mg/kg), magnesium (5.98 ± 0.05 mg/kg), and potassium (20.12 ± 0.07 mg/kg). Potassium and sodium were present in the highest quantity, while zinc occurred in the least amount. Lead and cadmium were not detected. The seeds of C. lanatus is a rich source (reservoir) of phytochemicals, macro- and micro nutrients.